2016
DOI: 10.7556/jaoa.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and Multimedia for Medical Education: A Landscape Review

Abstract: Many published studies suggest possible benefits from using gamified media in medical curriculum. This is a rapidly growing field. More research is required to rigorously evaluate the specific educational benefits of these interventions. This archive of hyperlinked tools can be used as a resource for all levels of medical trainees, providers, and educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
136
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 36 publications
0
136
0
17
Order By: Relevance
“…To conclude this section, we showed that gamifying anatomy education with some competitive elements succeeded in producing better academic grades. This was probably brought about by increased engagement, collaboration, mock clinical decision‐making and swift feedback (McCoy et al, )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude this section, we showed that gamifying anatomy education with some competitive elements succeeded in producing better academic grades. This was probably brought about by increased engagement, collaboration, mock clinical decision‐making and swift feedback (McCoy et al, )…”
Section: Discussionmentioning
confidence: 99%
“…How can this be done? While others have defined gamification broadly, including augmented reality (Ma et al, ; McCoy et al, ), we chose to define it as a platform not just for “digital games” per se but one comprising interventions such as flipped classroom (Chen et al, ) , self‐directed learning (SDL) (Sawatsky et al, ), script concordance testing (Cooke et al, ; Power et al, ), and use of apps as behavior modifiers (Gorgolewski et al, ; Lukhele et al, ). Students were incentivized to take part in the gaming by winning chocolate treats and also a book prize.…”
Section: Introductionmentioning
confidence: 99%
“…Other nursing education work has posited that there is no difference between gamified learning versus face-to-face clinical simulation [43]. Medical education research has found largely positive results regarding the use of gamification as a teaching-learning mechanism, in terms of medical content validity [27], acceptance of and retention of learned knowledge [44], and ongoing skill retention and learner engagement [29,45]. The growing importance and interest in this topic can also be inferred from the recent registration of a Cochrane Database of Systematic Review protocol, which plans to examine the effectiveness of serious gaming and other gamified interventions in health professional education [38].…”
Section: Discussionmentioning
confidence: 99%
“…While there has been much interest expressed in the use of serious games and gamification of eLearning tools (Ahmed et al, 2015;McCoy, Lewis, & Dalton, 2016;Nevin et al, 2014;(Graafland, Schraagen, & Schijven, 2012), we note that there has been little actual activity in this area. Graafland et al only found 30 examples of serious games in a systematic review and noted that most of these were not validated as educational tools.…”
Section: Discussionmentioning
confidence: 99%